Exemplary life : a theology of church life in Acts - Chambers, Andy. (Nashville, Tenn. : B & H Academic, 2012)
"Exemplary Life articulates Luke's vision for life together in a local church using key passages from Acts 2:42-47; 4:32-35; and 5:12-16 (known as 'summary narratives') as the starting point of reference. Although Luke is rightly acclaimed as the church's first historian, he was a powerful writer and theologian as well. He also planted churches with Paul and had definite convictions about what life together in the church should look like. Yet, Luke's theology of church life is underemphasized in modern scholarship, downplayed by issues rising from the historical-critical method. However, when the summary narratives are studied through the lens of narrative and rhetorical criticism, Luke's strategy is unmistakable. Those passages cast a vision for life together in an exemplary church, drawn from the historical circumstances of the church in Jerusalem. These narratives also serve as a starting point for studying church life throughout Acts. When the church planting movements in Samaria, Antioch, Ephesus, and Troas are examined, we find echoes of the narratives almost constantly. These amplify and drive home Luke's message in the summary narratives. Taking this path, twenty distinct characteristics of exemplary church life emerge. From repentance and Scriptural authority to praying together and earning the respect of neighbors, each one is thoughtfully presented here by author Andy Chambers to reassert Luke's voice in 21st century conversations about the faithful formation of New Testament churches." -- Publisher description.
How we lost Luke's theology of church life -- The rhetoric of summarization and exemplary church life in Acts -- Exemplary life portrait 1: Acts 2:42-47 -- Exemplary life portrait 2: Acts 4:32-35 -- Exemplary life portrait 3: Acts 5:12-16 -- Exemplary life in the Gentile churches of Acts -- A theology of church life in Acts -- Directions for application.
Includes bibliographical references (p. 169-199) and indexes.
Keywords: Bible. -- Study and teaching; Church growth; Church